Single mandibular implant study - denture satisfaction in the elderly - Passia, Nicole; Schwindling, Franz Sebastian (Journal of oral rehabilitation, 2017)
To investigate whether there are differences in patients’ denture satisfaction when an implant placed in the midline of the edentulous mandible is loaded either immediately or three months later, after second-stage surgery. One hundred and fifty-eight edentulous patients received a single implant in the midline of the mandible. After randomisation, it was loaded either immediately after implant placement (N = 81, group A) or three months later, after a submerged healing phase and a second-stage surgery (N = 77, group B). Patients’ denture satisfaction aspects were assessed, using visual analogue scales (VAS), before treatment, one month after implant placement during the submerged healing phase (only group B) and one and four months after implant loading. The statistical analysis was performed using the Wilcoxon signed-rank and rank-sum tests. One month after loading, a significant improvement in comfort, function and stability of the mandibular denture could be observed in both groups (P ≤ 0·05). A slight but not significant improvement was found between one and four months after loading. Patients with second-stage surgery and delayed loading rated the stability and fit of the mandibular denture as significantly better than patients who had immediate loading. A single implant in the edentulous mandible significantly increased patients’ denture satisfaction. After four months, stability and fit of the mandibular denture were considered better when a delayed loading protocol had been followed. A single mandibular implant in the edentulous mandible significantly increases patients’ denture satisfaction, regardless of the loading protocol.
Published online: 14 December 2016
Gesehen am 25.06.2018